Results of examination of patients with vascular optical and glaucoma neuropathy by means of Eysenck questionnaire - O. I. Lysenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Eysenck questionnaire was offered to 45 patients with vascular optical and glaucomaous neuropathy. The results showed that 40 patients (88.9 %) had melancholic temperament. These patients are demonstrated isolation, lability of the nervous system, instability in stressful situations and propensity to development of neuroses.